2010
DOI: 10.1007/s00384-010-0995-5
|View full text |Cite
|
Sign up to set email alerts
|

Prospective study of sexual dysfunction in men with rectal cancer: feasibility and results of nerve sparing surgery

Abstract: Our data show that nerve sparing technique can reduce the incidence of sexual dysfunction. Unfortunately, the technique is not applicable in every patient. Indications and techniques of autonomic nerve preservation are not standardized. Controlled trials with long-term follow-up seem to be necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0
4

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 19 publications
2
25
0
4
Order By: Relevance
“…ED in the patient with bilateral nerve sparing may have been associated with adjuvant radiochemotherapy and severe reactive depression subsequent to surgery. Taken together, our findings provide strong presumptive evidence that bilateral nerve sparing is an essential prerequisite for maintaining male EF, which is in accordance with previous studies of EF following nerve-sparing rectal cancer surgery [23,24]. It is of note that none of the patients reporting postoperative de novo ED had concomitant lower urinary tract or anorectal dysfunction.…”
Section: Discussionsupporting
confidence: 79%
“…ED in the patient with bilateral nerve sparing may have been associated with adjuvant radiochemotherapy and severe reactive depression subsequent to surgery. Taken together, our findings provide strong presumptive evidence that bilateral nerve sparing is an essential prerequisite for maintaining male EF, which is in accordance with previous studies of EF following nerve-sparing rectal cancer surgery [23,24]. It is of note that none of the patients reporting postoperative de novo ED had concomitant lower urinary tract or anorectal dysfunction.…”
Section: Discussionsupporting
confidence: 79%
“…Sexual dysfunction arises in the form of impotence and retrograde ejaculation [32]. In a study investigating the functions following the scarification of the anatomic nerve, it has been reported that inferior hypogastric plexus was related to impotence and superior hypogastric plexus was related to ejaculation [24,33].…”
Section: Discussionmentioning
confidence: 99%
“…They proposed that this was secondary to nerve injury in the hypogastric plexus and autonomic nerves encountered during the dissection of Denonvilliers fascia. Celentano et al 21 showed that avoiding macroscopic damage to nerves intraoperatively (nerve sparing) helps with preserving erectile function. Unfortunately, this technique is not applicable in every patient.…”
Section: Pelvic Surgerymentioning
confidence: 99%